Linking Internal Carbonate Chemistry Regulation and Calcification in Corals Growing at a Mediterranean CO2 Vent - Wall, Marlene; Prada, Fiorella; Fietzke, Jan; Caroselli, Erik; Dubinsky, Zvy; Brizi, Leonardo; Fantazzini, Paola; Franzellitti, Silvia; Mass, Tali; Montagna, Paolo; Falini, Giuseppe; Goffredo, Stefano (Frontiers in Marine Science, 2019)
Corals exert a strong biological control over their calcification processes, but there is a lack of knowledge on their capability of long-term acclimatization to ocean acidification (OA). We used a dual geochemical proxy approach to estimate the calcifying fluid pH (pHcf) and carbonate chemistry of a Mediterranean coral (Balanophyllia europaea) naturally growing along a pH gradient (range: pHTS 8.07–7.74). The pHcf derived from skeletal boron isotopic composition (δ11B) was 0.3–0.6 units above seawater values and homogeneous along the gradient (mean ± SEM: Site 1 = 8.39 ± 0.03, Site 2 = 8.34 ± 0.03, Site 3 = 8.34 ± 0.02). Also carbonate ion concentration derived from B/Ca was homogeneous [mean ± SEM (μmol kg–1): Site 1 = 579 ± 34, Site 2 = 541 ± 27, Site 3 = 568 ± 30] regardless of seawater pH. Furthermore, gross calcification rate (GCR, mass of CaCO3 deposited on the skeletal unit area per unit of time), estimated by a “bio-inorganic model” (IpHRAC), was homogeneous with decreasing pH. The homogeneous GCR, internal pH and carbonate chemistry confirm that the features of the “building blocks” – the fundamental structural components – produced by the biomineralization process were substantially unaffected by increased acidification. Furthermore, the pH up-regulation observed in this study could potentially explain the previous hypothesis that less “building blocks” are produced with increasing acidification ultimately leading to increased skeletal porosity and to reduced net calcification rate computed by including the total volume of the pore space. In fact, assuming that the available energy at the three sites is the same, this energy at the low pH sites could be partitioned among fewer calicoblastic cells that consume more energy given the larger difference between external and internal pH compared to the control, leading to the production of less building blocks (i.e., formation of pores inside the skeleton structure, determining increased porosity). However, we cannot exclude that also dissolution may play a role in increasing porosity. Thus, the ability of scleractinian corals to maintain elevated pHcf relative to ambient seawater might not always be sufficient to counteract declines in net calcification under OA scenarios.